The Relationship Between Prophetic Hadith and Intellect: A Critical Examination of the Scholarly Discourse - Rizapoor, Habiburrahman; Poya, Aminullah; Athari, Zaifullah (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
If the authenticity of a Hadith is uncertain and contradicts intellect, it can be deemed weak. However, if a Hadith is deemed authentic by Hadith scholars, two distinct theories emerge among Muslim scholars. The first theory argues that a correct Hadith never opposes the intellect. According to this perspective, a sound and clear intellect will never contradict an authentic Hadith. In contrast, the second theory posits that a prophetic Hadith should be considered weak if it conflicts with intellect. The study employs analytical and library research methods, drawing on a range of scholarly works including books, academic articles, and writings by Muslim scholars. The findings of this paper indicate that a Hadith, narrated through a strong chain of narrators tracing back to the Prophet, cannot inherently contradict the intellect. However, if a Hadith contradicts sound intellect, it can serve as a valid reason to question its authenticity and consider it weak. Through a comprehensive analysis of the scholarly discourse, this study provides a deeper understanding of the complex relationship between Hadith and intellect and how Islam values the intellect. It underscores the importance of rigorous authentication processes, emphasizing the need to consider the reliability of the Hadith chain and the principles of intellectual reasoning when assessing the strength or weakness of a prophetic Hadith.